SELF ESTEEM, SELF EFFICACY DAN PRESTASI AKADEMIK MAHASISWA AKUNTANSI: STUDI PADA KELAS PENGAUDITAN - Sidiq Ashari; Eka Noor Asmara; Supardi Supardi (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2019)
This study aims to provide empirical evidence of the related between self esteem and self efficacy with academic performance on auditing course. By using non-probability sampling techniques that is purposive sampling, this research using a sample of 194 university students in Yogyakarta that take on auditing course. This research model was developed based on previous research models by using survey in data collection process. Analysis uses structural equation models by using smartPLS software. Results of this research shown the support of 2 out of 3 proposed hypothesis, namely that there is a significant positive relationship between self esteem against self efficacy and academic performance. Meanwhile, this research can not proves that self efficacy strengthen academic performance on auditing course.